2020
DOI: 10.1111/iji.12506
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF‐a (rs361525 and rs1800629) with susceptibility to cervical intraepithelial lesion and cervical carcinoma in women from Republic of North Macedonia

Abstract: Cervical cancer (CCa) is one of the most common malign diseases in women associated with human papillomavirus (HPV). The virus is an initiating factor, but not sufficient for the development of cervical intraepithelial lesions (CIN) and CCa. The disease might be a result of the influence of host's genetic factors and polymorphisms in inflammatory‐related genes that modify the immune response to HPV and attribute to cancer susceptibility. We carried out a study to determine the association between TNF‐a‐238G/A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Behboodi et al, (2021) in a study among 153 Iranian cervical cancer cases and 292 free cancer subjects demonstrated that TNF-α rs1800629 was associated with increased level and risk of developing cervical cancer. However, Duvlis et al, (2020) reported that TNF-a-238G/A and TNF-a-308 G/T polymorphisms were not associated with the risk of HPV associated cervical intraepithelial lesions or cervical cancer cases in Macedonian women compared to controls. Moreover, Traore et al, (2020) revealed that TNF-308 G/A or IL18-607C/A polymorphisms were not associated with HPV infection among Burkina Faso women.…”
Section: Discussionmentioning
confidence: 95%
“…Behboodi et al, (2021) in a study among 153 Iranian cervical cancer cases and 292 free cancer subjects demonstrated that TNF-α rs1800629 was associated with increased level and risk of developing cervical cancer. However, Duvlis et al, (2020) reported that TNF-a-238G/A and TNF-a-308 G/T polymorphisms were not associated with the risk of HPV associated cervical intraepithelial lesions or cervical cancer cases in Macedonian women compared to controls. Moreover, Traore et al, (2020) revealed that TNF-308 G/A or IL18-607C/A polymorphisms were not associated with HPV infection among Burkina Faso women.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, the results of associations between TNF-α polymorphisms and cervical cancer are still controversial in different populations, even the same population. [6][7][8][9][10][11][12][13][14][15] For example, in 2001, Jang et al reported that the rs361525 A allele is a protective factor for cervical cancer in a Korean population. 13 In 2018, Li et al reported that the rs361525 A allele is a risk factor for cervical squamous cell carcinoma in a Chinese population from Shandong Province, Northern China.…”
Section: Introductionmentioning
confidence: 99%